Water Tunnel Turbulence Intensity Investigation For Micro-Hydrokinetic Turbine Application - Subramaniam, Viknaraj (Universiti Sains Malaysia, 2019)
Water tunnel is used to investigate the hydrodynamic behavior of immersed body in fluid dynamics study. Water tunnel is essential to provide a controlled condition for fluid flow research. The operational principle of water tunnel is identical to the wind tunnel but with different working fluid and higher flow-pumping capacity. Tests such as flow visualization in wind tunnel is more difficult to be conducted as turbulent flows in wind dissipate quickly whilst water tunnel is more suitable for such purpose due to higher fluid viscosity. However, the turbulence in the test section must be less than 10% or lower in order to produce a valid result. The present work focuses on improving the design criteria for each components and to maximize the performance of the water tunnel that was developed previously in terms of turbulence intensity reduction and improvement in flow uniformity. The design criteria of several primary components are studied and altered to reduce the turbulence intensity. The modified components were designed, fabricated and assembled to complete the modified water tunnel. This study also includes quantitative analysis on the velocity profiles and uniformity of the water flow at the test section. This is done by collecting data of the velocity at every point in the cross-section of water flow. That result was then used to plot the uniformity graph and to calculate the turbulence intensity in the water tunnel test section. The final turbulence intensity in the test section with the modifications made yielded a minimum result of 6.77%. The previous design yielded a turbulence intensity percentage of 9.66% comparatively. Thus, the turbulence intensity in the water tunnel was reduced by 29.92 %.